Exploring the Extinct Folk Art forms of Birbhum District, West Bengal, India - Niyogi, A. (University of Jaffna, 2024)
This seminar paper delves into the vibrant world of West Bengal's disappearing folk arts, focusing on three significant forms: Bhadu Gaan, Habu Gaan, and Patachitra. These art forms, deeply rooted in the cultural fabric of the region, hold immense historical, social, and artistic value, particularly within marginalized communities. This paper aims to unravel the intricate narratives, techniques, and symbolism embedded within Bhadu Gaan, Habu Gaan, and Patachitra. The paper begins by providing a historical overview of each folk art form, tracing its origins, evolution, and traditional significance. Special attention is given to the marginalized communities that have historically safeguarded and perpetuated these traditions, despite facing social and economic challenges. Furthermore, the paper explores the artistic techniques and stylistic elements characteristic of Bhadu Gaan, Habu Gaan, and Patachitra, shedding light on the craftsmanship and creativity involved in their creation. The paper highlights the unique aesthetics and storytelling methods employed by practitioners. Moreover, the paper discusses the contemporary challenges and threats faced by Bhadu Gaan, Habu Gaan, and Patachitra, including dwindling practitioners, diminishing patronage, and cultural commodification. It underscores the urgent need for concerted efforts to preserve and promote these endangered art forms, not only as cultural artifacts but also as vital components of West Bengal's intangible cultural heritage.
Keywords: Disappearing folk-arts; Rural art; Rural artists; Bhadu gaan; Habu gaan; Pata-chitra; Bahurupi